Digital possibilities and social mission in the voluntary sector: the case of a community transport organisation in the UK. (1st March 2020) - Walker, Tim; Esmene, Shukru; Colebrooke, Laura; Leyshon, Catherine; Leyshon, Michael
Abstract : Digital technology is seen as a panacea to meeting the financial and operational challenges faced by voluntary and community sector organisations (VCSOs), through delivering efficiencies and cost-saving, alongside improving quality of service. However, according to recent assessments in the UK, the rate of digital adoption is slow compared with other sectors. This article identifies how a VCSO in a period of austerity prioritises its social mission over functionality and efficiency gains from digital technology. Employing the heuristic of phronesis, we argue that VCSOs seeking to implement digital innovations need to strike a balance between instrumental rationality (that is, what is possible to achieve with technology) and value rationality (that is, what is desirable to pursue by VCSOs). Our key argument is that theories of value rationality provide a new explanation for the slow adoption of digital technology among VCSOs.